Wybrane prawnokarne zagadnienia związane z dokonywaniem płatności zbliżeniowej za pomocą cudzej karty płatniczej bez zgody osoby uprawnionej – uwagi na marginesie wyroku Sądu Najwyższego z 22 .3 .2017, sygn . akt III KK 349/16 - Tarapata, Szymon (Kwartalnik Prawa Publicznego, 2017)
In this article, the view of the Supreme Court was accepted that contactless payment by card for the goods without the consent of the authorized person fulfills the features of theft by breaking in (art. 279 § 1 c.c.). In the text a number of additional arguments was given which were not indicated in the Supreme Court`s judgment but can be a support for the point of view presented in it.